Colour Doppler sonography of hepatic haemangiomas with arterioportal shunts - Lim, K J (The British Institute of Radiology., 2012)
OBJECTIVES: To determine the frequency of intratumoural flow and peritumoural hepatofugal portal flow using colour Doppler sonography (CDS) on hepatic haemangiomas with arterioportal shunt (APS), and to investigate possible factors that may affect the capability of CDS to depict such findings. METHODS: The study included 45 patients (35 men, 10 women; mean age, 56 years) with hepatic haemangiomas with APS on CT or MRI. Locating the tumour on greyscale sonography, the depth, size and echogenicity of the tumour were evaluated. CT or MR images were evaluated for fatty liver. CDS was performed to determine the presence of intratumoural flow and peritumoural hepatofugal portal flow. Differences in frequency of intratumoural flow and peritumoural hepatofugal portal flow according to the depth, size, echogenicity and fatty liver were evaluated by Student’s t-test and Fisher’s exact test. RESULTS: On CDS, intratumoural flow and peritumoural hepatofugal portal flow were found in 66.7% and 60%, respectively. The tumour depth was the significant variable that affected the capability of CDS to depict such findings. The frequencies of intratumoural flow and peritumoural hepatofugal portal flow were as high as 88% and 80% for shallow (≤30 mm) lesions, and they were 40% and 35% for deep (>30 mm) lesions (p=0.0012; p=0.0051). CONCLUSION: CDS can commonly depict intratumoural flow and peritumoural hepatofugal portal flow in patients with hepatic haemangiomas with APS. Therefore, CDS should be routinely performed when an incidental mass is encountered during the screening sonography, especially when the lesion is shallow.